Transgenerational effects of chromium stress at the phenotypic and molecular level in Arabidopsis thaliana - Colzi, Ilaria; Gonnelli, Cristina; Vergata, Chiara; Golia, Gabriele; Coppi, Andrea; Castellani, Maria Beatrice; Giovino, Antonio; Buti, Matteo; Sabato, Tommaso; Capuana, Maurizio; Aprile, Alessio; De Bellis, Luigi; et al. (My University, 2023)
In this study, we describe the results obtained in a study of the transgenerational phenotypic effects of chromium (Cr) stress on the model plant species Arabidopsis thaliana. The F1 generation derived from parents grown under chronic and medium chronic stress showed significantly higher levels of the maximal effective concentration (EC50) compared with F1 plants generated from unstressed parents. Moreover, F1 plants from Cr-stressed parents showed a higher germination rate when grown in the presence of Cr. F1 plants derived from parents cultivated under chronic Cr stress displayed reduced hydrogen peroxide levels under Cr stress compared to controls. At lower Cr stress levels, F1 plants were observed to activate promptly more genes involved in Cr stress responses than F0 plants, implying a memory effect linked to transgenerational priming. At higher Cr levels, and at later stages, F1 plants modulated significantly fewer genes than F0 plants, implying a memory effect leading to Cr stress adaptation. Several bHLH transcription factors were induced by Cr stress in F1 but not in F0 plants, including bHLH100, ORG2 and ORG3. F1 plants optimized gene expression towards pathways linked to iron starvation response. A model of the transcriptional regulation of transgenerational memory to Cr stress is presented here, and could be applied for other heavy metal stresses.
Keywords: BHLH; Chromium; Heavy metals; Transgenerational priming; Stress memory; Transgenerational memory